An Analysis on Gender Representation in Cambridge Checkpoint English Coursebook - Dwina Mei Ekowati; Nurdin Noni; Haryanto Atmowardoyo (Har Press Indonesia, 2021)
The main focus of this study is to explore the representation of gender in Cambridge Checkpoint English Coursebook. The negative connotation of women stereotype in English Foreign Language (EFL) textbook potentially affects students’ negative perceptions and misconceptions about gender identity. The findings of previous studies on gender issues in language textbooks mostly indicate that they presented gender biases and stereotypes, but some studies reported positive images of women. To continue a critical discourse analysis (CDA) of EFL textbooks from a feminist perspective, the present study looks at visual and textual discourses representing images of women in EFL textbooks in Cambridge Checkpoint used by one private school in Makassar named Bina Citra Indonesia School. The findings reveal that the textbook represent gender stereotype in many Gender Analysis Pathway (GAP) area such as; gender GAP in culture area especially a stereotype of emotionally expressive woman and the stereotype of woman must be married at certain age, gender GAP in politic area, economic, health area and gender GAP in education area. Some gender discourses expressed by female characters and social actors. The result of research found that the textbooks support the continuation of gender biases and stereotypes. This textual study suggests that as English plays an increasingly important role in a transcultural and post-feminist world, the writers of English textbooks must pay attention to the issue of gender in language education.